Propedeutics of problematic issues in dissertation preparation as a factor in its successful defense (based on the study of pedagogical dissertations 2021–2025) - Fursa Iryna А. (University Pedagogical Journal, 2026)
This article discusses the possibilities and prospects for renewing the pool of researchers holding academic degrees in pedagogical sciences. Development trends in the pedagogical field of science from 2021 to 2025 are examined. It is noted that during this period, fewer researchers are choosing a professional career as an academic than in previous years. Meanwhile, the proportion of dissertation defenses that do not result in an academic degree remains stable. The significance of negative decisions on pedagogical dissertations is substantiated and the reasons for these decisions are analysed. Taking these into account by graduate students and their supervisors could contribute to a long-term reduction in this indicator.